Massive carbon storage in convergent margins initiated by subduction of limestone - Chunfei Chen (Nature Portfolio, 2021)
Experiments and buoyancy calculations reveal that subduction of limestone results in massive carbon storage in arc lithosphere, forming an important carbon reservoir in convergent margins. Remobilization of this carbon reservoir during arc magma ascent may dominate carbon emissions at volcanic arcs.